Institutional quality and macrofinancial resilience in Asia - Beirne, John,Panthi, Pradeep (Asian Development Bank Institute, 2022)
This paper examines the effect of institutions on macrofinancial resilience in Asia. Focusing on a panel of 12 Asian economies from 1996Q1 to 2020Q4, we find that institutions for economies with high levels of institutional quality support the resilience of real GDP per capita and net FDI inflows during periods of elevated financial stress. In addition, our results suggest resilience due to institutions for these economies regarding net equity and debt inflows in crisis times, also reflecting portfolio rebalancing effects. For economies with lower levels of institutional quality, institutions may help to stabilize portfolio debt during crisis times, although the magnitude of the effects are small. As well as pointing towards resilience thresholds in institutional quality, our paper provides insights on critical sub-components of overall institutional quality, notably rule of law, political stability, and regulatory quality. The findings help to inform the direction of policy efforts towards strengthening institutional capacity, and structural reforms for enhancing economic development and resilience to shocks.
10419/267769
Keywords: Graue Literatur; institutional quality; economic development; international capital flows; Asia